Globalization and Changing Relations among Market, State and Civil Society: A Comparative Analysis of Patagonia and Iowa - Butler Flora, Cornelia; Bendini, Monica (The International Journal of Sociology of Agriculture and Food, 2007)
Vertical integration by means of an industrial (as opposed to market) convention is a major corollary of neo-liberal globalization. In both the U.S. Midwest and southern Argentina, the type of agriculture that displaced the native peoples was family scale production based on the market convention: price based on volume. From the 1940s to the mid-1990s family producers of hogs in Iowa and of apples in Río Negro went from independent producers with multiple marketing options to displacement by vertically integrated global companies that demanded particular characteristics in the product. Their varied modes of resistance to vertical integration and the industrial convention demonstrates possibilities from the center and the semi-periphery, show how market, state, and civil society could be mobilized to create and control alternative agricultural food networks based on domestic and civic conventions. Because of different sources of prime vulnerability, labor in Río Negro and the environment in Iowa, mechanisms of vertical integration are differentially effective. Thus multinational corporations sought different strategies to maximize control of the value chain in order to guarantee particular product characteristics while minimizing liability from potential violation of labor and environmental laws. In each setting the integrated multi-national firms attempted both direct ownership and contracting, and found less resistance through contracting. Different involvement of civil society determined the success of the implementation of civic conventions that could maintain family-managed production.